MODEL KERJASAMA ACADEMIC, BUSINESS, GOVERMENT DAN CIVIL SOCIETY PADA KEBIJAKAN KERTAJATI AEROCITY - Waluyo Zulfikar (Universitas Jenderal Ahmad Yani, 2019)
West Java Provincial Government in order to create innovation in order to accelerate the achievement of the vision of the Governor of West Java through the development of a strong regional economic structure. The innovation in question is to produce policies in the form of Regional Regulation Number 13 of 2010 concerning the Development and Development of West Java International Airport and Kertajati Aerocity. Various efforts have been made by the West Java Provincial government in order to accelerate the development of BIJB. The problem led to problems in land acquisition which was hampered by the rejection of some residents of the implementation of the BIJB and Kertajati Aerocity development. Another problem also arises related to the analysis of the readiness of the BIJB as the manager and support of the government in implementing BIJB and Kertajati Aerocity policies and related to the carrying capacity of water resources which are important for the sustainability of the existence of an area which is taken into consideration for implementing BIJB and Kertajati Aerocity in Majalengka Regency. West Java province. This basically requires qualified strategic steps for the realization of Kertajati aerocity in Majalengka Regency. The collaboration model of academic, business, government and civil society on Kertajati Aerocity policy is ultimately deemed qualified to realize aerocity Kertajati programs and policies. Keywords: BIJB, Regional Cooperation, Majalengka Regency